2016
DOI: 10.1590/s0102-053620160421
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic performance of sweet potato with different potassium fertilization rates

Abstract: Sweet potato is a vegetable with great potential due to its versatility of use, which covers human food, animal feed and biofuels. However, it is still little studied, especially regarding mineral nutrition and potassium. Thus, a study was conducted to evaluate potassium fertilizer doses (0, 30, 60, 90, 120 and 150 kg/ha K 2 O) on mineral nutrition and yield of 'Beauregard' sweet potato in a typic Hapludult soil with low K level (0.3 mmol c /dm 3 ). The experimental design was of randomized blocks with four r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The application of 240 and 183 kg ha −1 K 2 O divided between plantings plus 3 MP also provided yields similar to treatments with three K application times, and the response to K application rates was greater when the K application was split. When K application occurred exclusively at planting, other studies also reported a lower response of sweetpotatoes to K rates in K‐deficient soils (Cecílio Filho et al., 2016; Nascimento et al., 2019). According to Nogueira et al.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…The application of 240 and 183 kg ha −1 K 2 O divided between plantings plus 3 MP also provided yields similar to treatments with three K application times, and the response to K application rates was greater when the K application was split. When K application occurred exclusively at planting, other studies also reported a lower response of sweetpotatoes to K rates in K‐deficient soils (Cecílio Filho et al., 2016; Nascimento et al., 2019). According to Nogueira et al.…”
Section: Discussionmentioning
confidence: 97%
“…Brazilian guidelines for sweetpotato fertilization in K‐deficient soils recommend K application rates between 90 and 120 kg ha −1 K 2 O (Casali, 1999; Echer et al., 2015; Lorenzi et al., 1997; Silva et al., 2002). However, in Brazilian K‐deficient soils, positive productive responses of sweetpotatoes were observed up to 85 kg ha −1 K 2 O when K fertilizer was applied exclusively at planting (Cecílio Filho et al., 2016; Nascimento et al., 2019), and positive responses were observed up to 174–180 kg ha −1 K 2 O when K was split applied (Brito et al., 2006; Nogueira et al., 1992). However, in the case of K‐deficient soils, our results showed that if K fertilization was split applied three times, the total and marketable sweetpotato root yield increased up to 153 and 179 kg ha −1 K 2 O, respectively, with no further response to higher K application rates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations